Mechanical properties of foam-filled auxetic circular tubes: Experimental and numerical study. (January 2022) - Ren, Xin; Zhang, Yi; Han, Chuan Zhen; Han, Dong; Zhang, Xiang Yu; Zhang, Xue Gang; Xie, Yi Min
Abstract: In this paper, rigid polyurethane (PU) foam was filled into hollow auxetic tube for enhancing the energy absorption. The rigid PU foams and stainless-steel auxetic tube with different geometrical parameters were manufactured, respectively. They were then assembled to form composite foam-filled auxetic tube (FFAT). Four auxetic tubes and four FFATs were respectively tested to examine the enhancement of energy absorption. Tubular types and the effects of parameters including wall thickness, and ellipticity, on FFATs were analyzed numerically by using the validated models. The results show that the overall absorbed energy of FFAT is larger than the sum of single foams and hollow auxetic tube under compression. The geometrical parameters of wall thickness, ellipticity, have a considerable effect on the structural deformation mode and energy absorption. These findings could promote the applications of auxetic composite structures in protective engineering. Highlights: The first polyurethane foam-filled auxetic tubes (FFAT) are designed, fabricated and investigated. The proposed FFATs could exhibit superior mechanical properties under axial compression. The findings are useful to guide the design of advanced tubular structures for energy absorption.